2013
DOI: 10.1149/2.031309jes
|View full text |Cite
|
Sign up to set email alerts
|

Molten Carbonates as an Effective Oxygen Reduction Catalyst for 550–650°C Solid Oxide Fuel Cells

Abstract: We report the first study that investigates the use of molten carbonates as an effective catalyst to promote electrochemical oxygen reduction reaction (ORR) at the cathode of intermediate temperature solid oxide fuel cells (IT-SOFCs). A series of binary Li-K carbonate compositions were incorporated into the porous backbones of a commercial cathode assembled in symmetrical impedance cells for electrochemical characterization. Within the temperature range of 550-650 • C, we observed that the polarization and ohm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…3 we conclude that the best rate-limiting mechanism describing the CO 2 transport through a metal-carbonate membrane follows the formation of CO 4 2 À . In fact, the existence of CO 4 2 À has been experimentally observed by in-situ Raman spectroscopy [22], and theoretically confirmed by DFT modeling [23].…”
Section: Experimental Results Vs Mechanismsmentioning
confidence: 75%
See 1 more Smart Citation
“…3 we conclude that the best rate-limiting mechanism describing the CO 2 transport through a metal-carbonate membrane follows the formation of CO 4 2 À . In fact, the existence of CO 4 2 À has been experimentally observed by in-situ Raman spectroscopy [22], and theoretically confirmed by DFT modeling [23].…”
Section: Experimental Results Vs Mechanismsmentioning
confidence: 75%
“…4(a) illustrates schematically each elementary step involved in the chargetransfer process. In general, molten carbonate (MC) can provide a "soft" surface for O 2 molecules to stick on [18,19,23], and further allow O 2 to chemically dissolve into MC as CO 4 2 À through Eq. (5-1).…”
Section: A New Co 2 Transport Modelmentioning
confidence: 99%
“…Latterly, they found that the presence of C 2 O 5 2À and CO 4 2À intermediate species confirmed by the Raman spectroscopy measurement facilitated the CO 2 transportation [121]. Continuous works from the same group from both experimental and theoretical aspects showed that those intermediate functional groups are also vital for ORR in the cathode for ceria-carbonate electrolyte based fuel cells [114,[122][123][124]. In fact, the ORR step is the most energy loss process in the whole fuel cell processes.…”
Section: Oxygen Reduction Promotermentioning
confidence: 98%
“…(a) Electrochemical impedance spectra comparison of symmetric cells with various molten carbonate additives at 600 °C, (b) and (c) molten carbonate loading dependence of polarization resistance and ohmic resistance of LSCF‐GDC/LSGM/LSCF‐GDC symmetrical cells at 550–600 °C, respectively, and (d) proposed global ORR reaction process at molten carbonate added cathode, LSFC and LSGM are model cathode and electrolyte, respectively . Reprinted with permission from the Electrochemical Society.…”
Section: Role Of Carbonatementioning
confidence: 99%
“…However, the exact reaction mechanism at the cathode is still doubtful because several conclusions have been claimed about the reaction mechanism at the cathode, such as the peroxocarbonate mechanism 2,31 or mixed of superoxide and peroxide mechanism. …”
Section: Analysis Of the Reaction Mechanism-mentioning
confidence: 99%